KamLAND-experiment and soliton-like nuclear georeactor - V. D. Rusov; D. A. Litvinov; S. Cht. Mavrodiev; E. P. Linnik; V. N. Vashenko; T. N. Zeletsova; M. E. Beglaryan; V. A. Tarasov; I. V. Sharph; S. A. Chernegenko; V. P. Smolyar; P. A. Molchinikolov; et al. (Ukrainian Antarctic Journal, 2010)
We give an alternative description of the new data produced in the KamLAND experiment, assuming the existence of a natural nuclear reactor on the boundary of the liquid and solid phases of the Earth's core. Analyzing the uncertainty of antineutrino spectrum of georeactor origin, we show that the theoretical (which takes into account the soliton-like nuclear georeactor with power about 20 TW) reactor antineutrino spectrum describes with good accuracy the new experimental KamLAND-data. At the same time the parameters of mixing ( Δm212 =2.5х10-5 eV2, tan2Θ12 =0.437) calculated within the framework of georeactor hypothesis are substantially closer to the data of solar flux SNO-experiment then the parameters of mixing obtained in KamLAND-experiment.